TUTORIAL PEMBUATAN SABUN CAIR MELALUI MULTIMEDIA UNTUK MEMOTIVASI WIRAUSAHA PANTI ASUHAN - Uminingsih, Uminingsih; Harmastuti, Harmastuti (LPPM IST AKPRIND Yogyakarta, 2023)
Submission of tutorials for the socialization of making liquid laundry soap through multimedia videos followed by direct practice by viewers is easier to do. Meanwhile, video editing is done using Adobe Premiere Rush software, producing good pictures as well as sound. One of the problems in managing an orphanage is how to prepare the residents of the orphanage to live independently after graduating from high school and not living in an orphanage anymore. The solution is to provide formal education in science through formal schools, and additional education on morals and religious worship by the Foundation. Apart from that, it is very necessary to provide insight into entrepreneurship to provide motivation for the willingness to be entrepreneurial or self-employed to foster self-confidence in being able to live independently when one day after leaving the orphanage. As an implementation through the practice of making liquid laundry soap which is easy to make and has a promising economic value. on a home industry scale. From the research results, there are about 85% of the profit earned for each liter of laundry soap produced, when compared to liquid laundry soap sold in packages that already have a name. The resulting liquid laundry soap can be used to open a business selling laundry soap liquid or as a raw material for the type of business receiving laundry. With this provision of skills, it is hoped that it will be able to lead the young residents of the orphanage to be able to live independently after leaving the orphanage in the future.